Digital Health Innovation and Public Trust in Pandemic Preparedness - Nirwan, Multy Syaddam; Arwan; Syam, Sadli; Firmansyah; Syahrir, Muhammad Sabri; Satria, Muhammad Aji; Hilintang, Rendhar Putri (Indonesian Scientific Publication, 2024)
This narrative review examines the role of digital health technologies and big data analytics in pandemic preparedness, with particular reference to COVID-19. The objective was to synthesize evidence on how technological innovations supported healthcare and education during crises and to identify barriers that limit their effectiveness. Literature searches were conducted across PubMed, Scopus, Web of Science, and Google Scholar, focusing on empirical studies, case analyses, and systematic reviews related to telehealth, artificial intelligence, digital dashboards, and citizen science initiatives. The review found that digital innovations enabled remote consultations, predictive modeling, and real-time monitoring, which reduced pressure on health systems and informed public policy. Evidence highlighted the value of visual analytics and community-driven data in filling information gaps. However, infrastructural limitations, weak governance, and low public trust constrained adoption, particularly in low- and middle-income countries. Comparative analyses showed that countries with strong infrastructures and transparent policies, such as Taiwan and South Korea, achieved more effective outcomes than regions with limited technological readiness. These findings indicate that digital health tools are powerful enablers of crisis response but insufficient in isolation. Sustainable integration requires investment in infrastructure, capacity-building, transparent communication, and participatory approaches. Embedding these reforms into health systems will be critical to ensure equitable access, strengthen resilience, and optimize the benefits of technological innovation for future pandemic preparednessof technological innovations in global health preparedness.